The Role of Green Human Resource Management Practices in Supporting Social ReSponsibility in Governmental Services Sector at Emirate of Ajman - ElSawy, Mahmoud; Aldabbagh, Tamador (The Arab Journal of Administration, 2021)
ABSTRACT The current study focuses mainly on Characterization of both GHRM Practices and Social Responsibility dimensions in governmental Services Sector at Emirate of Ajman as well as determining the nature and the type of the relationship between the dimensions of green human resources management practices and the Dimensions of social responsibility in addition to specifying how to improve the level of social responsibility by paying attention to green human resource management practices. To achieve this, survey was distributed to a sample of 135 respondents working at human resource management departments in the governmental Services Sector at Emirate of Ajman, The results showed that there are statistical significance differences between employees’ awareness of the variables of green human resources management practices according to different demographics characteristics. The results also revealed that there are statistically significant differences between the practices of green human resources management and the level of social responsibility practices, and this relationship is positive and statistically significant. The researchers have come up with a set of recommendations to enhance the level of social responsibility by adopting green human resource management practices.